Hidden Lineages in the Mountains: The Genus Glyptaulax Gude, 1914 and Maelamaodiscus gen. nov. (Heterobranchia: Stylommatophora: Charopidae and Ariophantidae) with Description of Two New Species from Western Thailand - Sutcharit, Chirasak; Pholyotha, Arthit (Tropical Natural History, 2023)
The Tenasserim Range runs from north to south and forms not only a natural border between Thailand and Myanmar, but also the backbone of the Indo-Burma biodiversity hotspot, which is rich in endemic species, especially of the malacofauna. Knowledge of land snail diversity in Thailand is continuously expanding and being refined, and various groups have been revised recently. From field surveys throughout the country, unique snails with delicate shell shape and sculpture hidden in mountainous areas have been discovered and described. Firstly, a new species of the Charopidae, Glyptaulax spectabilis sp. nov. has round tubercles arranged on spiral ridges. Second, Maelamaodiscus somsakpanhai gen. et sp. nov. of the Ariophantidae is described from the Moei River Basin. These new taxa differ from all Southeast Asian ariophantids by having a prominent radial ridge, peculiar aperture with wide sinulus, and an impression on the last whorl. This discovery of endemic taxa reflects the high biodiversity in this region, and suggests that many more land snail treasures are still waiting to be revealed.